THE CRIME OF MURDER THROUGHOUT THE HISTORY OF CRIMINAL LAW (Heritage, 2023)
Human life and body represent social values that have always been and remain the subject of criminal protection. Studying different historical eras, one can conclude that life and body of members of certain social classes was not subject to criminal protection, and in certain eras legal protection of life and body was not equally provided to everyone.The constant development of society and changes in all spheres led to the need formore and more contact between people, and their relationships came to various passings and the desire to be resolved in their own way. Conflict situations led to mutual attacks in order to resolve the situations that arose which ended with an attack and endangering the physical integrity of people.The work contains the analysis of the criminal offense of murder throughout the history of criminal law, and includes the old and the Middle Ages, where the place of the crime of murder is discussed in Hammurabi’s Code, the Law of Plate XII, Koran, Russian justice and further up to modern times.
Keywords: murder, murderer, guilt, law, punishment.